Laser-Generated Functional Nanoparticle Bioconjugates Design for Application in Biomedical Science and Reproductive Biology - Barchanski, Annette (Springer Fachmedien Wiesbaden : Imprint: Springer Spektrum, 2016)
Annette Barchanski deals with the question how to design nanoparticles for biomedical research. She considers properties such as size, charge, biocompatibility, and functionalization of nanoparticles from a biologist's point of view in order to achieve specific cellular responses. The author discusses the structure-function relationship of nanoparticle conjugates derived from a laser-based fabrication method. Both the limits and perspectives of tunable conjugate functions are presented, providing a general outline for researchers to configure functionalized nanoparticles with a specifically optimized design for biomedical requests, e.g. in biomedical engineering regenerative science and reproductive biology. Contents Nano-Revolution of Biomedical Science and Reproductive Biology Gold Nanoparticles: Optical and Toxicological Aspects; Membrane Interactions; Biological Application Areas Design Criteria and Laser-BasedFabrication of Gold Nanoparticles and Gold Nanoparticle Bioconjugates Yield Enhancement of Laser Ablation Method Structure-Function Relationship: Intrinsic Parameters of Gold Nanoparticles; Conjugation Parameters Laser-Based Fabrication and Bioconjugation of Silicon and Magnetic Nanoparticles Target Groups Researchers and students in the fields of nanotechnology, biomedicine, chemical engineering, laser technology, reproductive biology, and toxicology The Author Annette Barchanski works as a scientific researcher at the Laser Zentrum Hannover e.V.